Selective strain incorporation and retention into Si-substrate through VLS growth of TiO2 nano-islands. (7th February 2017) - Palit, Mainak; Chowdhury, Basudev Nag; Das, Avishek; Das, Souvik; Chattopadhyay, Sanatan
Abstract: In this work, process induced strain has been incorporated selectively into Si-substrate by growing TiO2 nano-islands on it using vapour–liquid–solid method and the induced strain has been retained by chemically removing the TiO2 nano-islands. The retained strain is quantified by employing pole study method of the electron backscatter diffraction (EBSD) and compared with the similar results obtained from micro-Raman measurements. A very good agreement between the results indicates accuracy of the developed pole study analyses. Both the methods suggest that such a low-cost approach is capable of incorporating and retaining a compressive strain >4.7% along 〈 1 0 0 〉 and tensile strain >1.3% along 〈 0 1 0 〉 and 〈 0 0 1 〉 directions by growing the crystalline TiO2 nano-islands on Si substrates followed by their chemical removal.